Negative effect of ectoparasite burdens on the condition factor from farmed tilapia Oreochromis niloticus in the Yucatan, Mexico - Paredes-Trujillo, Amelia; Velázquez-Abunader, Ivan; Papiol, Vanesa; del Rio-Rodríguez, Rodolfo E.; Vidal-Martínez, Víctor Manuel (Veterinary parasitology, 2021)
•The ectoparasitic burden have negative effect on condition factor of the Nile tilapia.•The fish with low K values (K≤ 0.25) were associated with a high ectoparasitic burden (295 ± 191).•Cichlidogyrus genus, Trichodina sp. and G. cichlidarum showed a negative effect in K values.•Ectoparasites can be responsible of loss up to 12–15 % in profit margin per ton of fish. Nile tilapia (Oreochromis niloticus Linnaeus, 1758) is one of the most important aquaculture species in the world, and, when introduced, the ectoparasites of Nile tilapia have followed. Currently, farmers worldwide consider these ectoparasites harmless, but intensities can reach up to 1000 individuals per fish in tropical regions. In this cross-sectional study, we used the condition factor to estimate the potential effects of low (45 ± 31 ectoparasites per fish) and high (295 ± 191) ectoparasitic burdens across 28 tilapia farms and included the analysis of the effects of 44 management and environmental variable from the farms. A stepwise procedure in a multiple linear regression analysis retained the variables that explained the most variance, which was the ectoparasitic burden (57 %). We found significantly higher values of the condition factor in Nile tilapia with low ectoparasitic burden than in those with high ectoparasitic burden. Additionally, Nile tilapia with a high ectoparasitic burden weighed less than half than those with a low burden (102 ± 105 g versus 230 ± 128 g, respectively). We also found a significant non-linear, negative relationship between the ectoparasitic burden and the relative condition factor values per fish, which was most likely due to an increase in gill mucus caused by the ectoparasitic burden that depleted energy in the Nile tilapia. The economic consequence of the ectoparasitic burden translated roughly into a loss up to 12–15 % in profit margin per ton of fish, based on the price of Nile tilapia in the Mexican market.